The role of utrophin in the potential therapy of Duchenne muscular dystrophy. - Perkins, K; Davies, K (2002)
Duchenne muscular dystrophy is an X-linked recessive muscle wasting disease caused by the absence of the muscle cytoskeletal protein, dystrophin. Dystrophin is a member of the spectrin superfamily of proteins and is closely related in sequence similarity and functional motifs to three proteins that constitute the dystrophin related protein family, including the autosomal homologue, utrophin. An alternative strategy circumventing many problems associated with somatic gene therapies for Duchenne muscular dystrophy has arisen from the demonstration that utrophin can functionally substitute for dystrophin and its over-expression in muscles of dystrophin-null transgenic mice completely prevents the phenotype arising from dystrophin deficiency. One potential approach to increase utrophin levels in muscle for possible therapeutic purpose in humans is to increase expression of the utrophin gene at a transcriptional level via promoter activation. This has lead to an interest in the identification and manipulation of important regulatory regions and/or molecules that increase the expression of utrophin and their delivery to dystrophin-deficient tissue. As pre-existing cellular mechanisms are utilized, this approach would avoid many problems associated with conventional gene therapies.